A rare cause of bilateral exophthalmos: about one case with a sphenoid mucocele - N. Pilor (Rhinology Online, 2020)
Background: Mucocele is a benign cystic pseudo-tumor that develops within the sinus cavities. The most frequent locations are frontal and frontoethmoidal. The sphenoidal forms are rare. We report a case of sphenoidal mucocele revealed by bilateral exophthalmos. Methods and results: We report the case of a 14 year old male patient, without any particular pathological history, referred by his ophthalmologist for bilateral nasal obstruction, bilateral exophthalmos and visual acuity decrease evolving since one year. The ENT examination found a large, renitrant mass, filling the entire right nasal cavity. This mass pushed the nasal septum to the left. The CT scan showed a large sphenoidal, hypodense mass evoking a mucocele. The patient underwent endonasal marsupialization by endoscopic guidance. Conclusions: Sphenoidal mucocele is a rare cause of bilateral exophthalmos. The diagnosis can be misplaced when the signs are overt extra-sinus. Hence the interest of CT in order to eliminate other differential dignostics.